Impact of distillery spentwash irrigation on the yield of Jasmine (Oleaceae) flowering plant - Chandraju, S; Thejovathi, C; Chidan Kumar, C S (Current Botany, 2013)
The yields of Jasmine (Oleaceae) flowering plant was investigated by irrigated with different concentrations distillery spentwash. Primary treated spentwash (100% 1:1, 1:2, and 1:3) was analyzed for plant nutrients such as nitrogen, phosphorous, potassium and other physical and chemical characteristics. Soil was tested for chemical and physical parameters. Jasmine (Oleaceae) sets were planted in different pots and irrigated with raw water (RW), 1:1, 1:2 and 1:3 spentwash. The nature of yields was studied. It was found that the yields of plant was very good (100%) in 1:3 SW irrigation, while very poor (25%) in 1:1 SW, moderate (80%) in 1:2 SW and 95% in RW irrigation growth.